Latilactobacillus curvatus: A Candidate Probiotic with Excellent Fermentation Properties and Health Benefits - Chen, Ying (Foods, 2020)
Latilactobacillus curvatus is a candidate probiotic that has been included in the list of recommended biological agents for certification by the European Food Safety Authority. According to the published genomic information, L. curvatus has several genes that encode metabolic pathways of carbohydrate utilization. In addition, there are some differences in cell surface complex related genes of L. curvatus from different sources. L. curvatus also has several genes that encode bacteriocin production, which can produce Curvacin A and Sakacin P. Due to its ability to produce bacteriocin, it is often used as a bioprotective agent in fermented meat products, to inhibit the growth of a variety of pathogenic and spoilage bacteria. L. curvatus exerts some probiotic effects, such as mediating the production of IL-10 by dendritic cells through NF-κB and extracellular regulated protein kinases (ERK) signals to relieve colitis in mice. This review is the first summary of the genomic and biological characteristics of L. curvatus. Our knowledge on its role in the food industry and human health is also discussed, with the aim of providing a theoretical basis for the development of applications of L. curvatus.